Economical Blood Pressure Monitoring System For Telemedicine Applications - et. al., G Raja Kullayappa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Telemedicine and periodic patient monitoring provide medical assistance for people in remote locations. For this hassle free health monitoring systems are required at an affordable cost. In this work, electrocardiogram (EKG) and photoplethysmography (PPG) based blood pressure monitoring device is developed, and the system results are compared with the standard instruments. The EKG of the patients is obtained from the AD8232 sensor, and PPG is captured using the MAX30101. The R peaks of EKG, the peaks, and the valley points of the PPG are used for finding the Pulse Transit Time (PTT). The PTT is calibrated against the standard sphygmomanometers to find the blood pressure. The PPG signal is calibrated to calculate the arterial oxygen saturation levels of the patient and the frequency of the EKG peaks is calculated for obtaining the heart beat rate. The results are displayed on the displaying unit and are stored in the IoT cloud platform for remote access. The accuracy of Heart rate is recorded at ± 2BPM, SaO2 at ± 2.5% Systolic BP at ± 5mmHg and Diastolic BP ± 5mmHg.